Block Copolymer Thin Films: Self-Assembly of Large Molecular Weight Systems and the Fabrication of Novel Metal/Metal Oxide Nanomaterials - Selkirk, Andrew David (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
The self-assembly of block copolymers (BCPs) is considered an excellent candidate to further the development and progression of nanoscale technologies. While lithographic applications remain a primary topic of focus for BCP research, less conventional areas of interest such as optics, catalysis, and sensing present unique challenges to the field. In the case of these aforementioned areas, the advantages of BCP-templated nanostructures include low cost, high scalability, morphological tunability, and large-area ordering. This thesis reports the development of an innovative strategy for the self-assembly of large BCP systems with optics- scale dimensionality, along with expanding the potential of BCP templating via fabricating novel catalytic and sensing materials. Firstly, the rapid self-assembly of a large BCP system (poly(styrene)-b-poly-2-vinylpyridine (PS-b-P2VP)) into lamellar domains via a controlled solvent vapour annealing (SVA) strategy is detailed. The influence of variables such as the film thickness, SVA time and the rate of swelling on the morphology of the BCP system are analysed. A liquid phase infiltration (LPI) strategy is utilised to convert the lamellar BCP films into a metal oxide hardmask, which is then etched into a Si substrate to create large period nanowall features. The resulting self-assembled BCP films are also utilised for synthesizing 3- dimensional metallic lamellae, again using a LPI strategy. The relationship between the BCP film thickness on the heights of the metal structures is detailed, enabling precise control over the heights of the nanowall structures. These structures are utilised as photocatalytic structures for the degradation of methyl orange, revealing a height-dependent performance relationship. Finally, a novel, multifunctional catalytic device is fabricated and characterised using BCP templating. A PS-b-P4VP BCP system is self-assembled into cylindrical domains on an indium-tin oxide (ITO) substrate via SVA, which is then converted into WO3 nanowires using a LPI strategy. The device is successfully utilised for both water oxidation and highly selective epinephrine detection.
APPROVED
Keywords: block copolymer; self-assembly; liquid phase infiltration; pattern transfer; solvent vapour annealing